Accelerated surface reconstruction via a controllable boronization strategy for efficient water oxidation - Wankun Li; Meijia Liu; Shuo Zheng; Yongjia Li; Yujia Liu; Lin Wu; Shuai Chen; Lixiang Li; Chengguo Sun; Han Zhang; Baigang An (Fuel, 2027)

Unlocking the Size-Dependent mechanism of CO2 reduction on Carbon-Supported Nin clusters - Yimeng Sun; Lin Tao; Meixu Lu; Xin Quan; Mingjie Wu; Javed Rehman; Nan Wang; Lixiang Li; Baigang An (Fuel, 2026)

Why does tropical cyclone Emeraude move along a small annular track? - Yaoyao Zhou; Lixiang Shen; Ziqiong Cheng; Lin Peng; Rufa’i Isyaku; Haibin Lü (Journal of Earth System Science, 2026)

Enrichment of organophosphate esters in the surface microlayer of a subtropical urban lake: Phase partitioning dynamics and air-water exchange implications - Mingfu Lin; Tao He; Rong Wang; Lixiang Zhong; Menghuan Zhang; Jun Wang; Yumei Huang (Journal of Hazardous Materials, 2026)

The synergistic effects of UV-328 and polystyrene microplastics on zebrafish embryos: developmental toxicity, oxidative stress, and neurotoxicity - Xinlu Yang; Xinyi Liao; Lixiang Zhong; Mingfu Lin; Menghuan Zhang; Jun Wang; Yumei Huang (Aquatic Toxicology, 2026)

An integrated multi-algorithm analysis to decipher senescence and metabolic characteristics in nucleus pulposus cells during disc degeneration - Zhuangyao Liao; Ming Li; Ziyu Chen; Zhi Yao; Yuluan Wu; Zhen Tan; Junyu Qian; Chunyuan Yang; Lin Huang; Lixiang Xue; Deli Wang (GeroScience, 2025)
Accumulating evidence has suggested that intervertebral disc degeneration (IVDD) serves as a health problem deserving attention from worldwide, owing to the low back pain and even disability it causes. Cellular senescence, an irreversible process of terminal cell cycle arrest, plays an essential role in the degeneration of nucleus pulposus (NP) cells and IVDD with an unknown underlying mechanism. Here, we have explored the senescence signature in IVDD through high dimensional weighted gene co-expression network analysis (hdWGCNA) algorithm in two single cell datasets (PRJCA014236 and GSE244889) to construct a novel signature called NP_Senescence, which accurately identifies the patients with IVDD. The efficacy and accuracy were validated in various external datasets, including two expression array datasets (GSE70362 and GSE34095) and one single cell dataset (GSE230809). Additionally, the accuracy of the specific model was also verified with the senescent cell identification (SenCID) algorithm. IVDD patients with a high NP_Senescence score exhibited the characteristics of compensated activation of hyaluronic acid monomers synthesis and abnormal status of DNA damage repair through single-cell Flux Estimation Analysis (scFEA) algorithm. Furthermore, the NP_Senescence was negatively associated with the level of AMP and Glucose-1-phosphate, while positively associated with the level of β-alanine and UDP-glucuronic acid. In conclusion, we constructed a novel disc-specific scoring model NP_Senescence by comprehensively analyzing the senescence-related genes of IVDD, which can be used for patient early diagnosis and treatment, as well as the identification of metabolic characteristics.

Exploring the combined toxic effects of tri-n-butyl phosphate and polystyrene micro/nano-plastics on Daphnia magna under environmentally relevant concentrations - Lixiang Zhong; Xiaoli Chen; Menghuan Zhang; Mingfu Lin; Jun Wang; Yumei Huang (Environmental Geochemistry and Health, 2025)

Airborne Microplastic Pollution in a Highly Urbanized City: Occurrence, Characteristics, Human Exposure and Potential Risks - Yijing Gan; Xinlu Yang; Lixiang Zhong; Xinyan Chen; Mingfu Lin; Xian Qing; Laiguo Chen; Jun Wang; Yumei Huang (Water, Air, & Soil Pollution, 2025)

Intercropping improves plant biochemistry and soil microecology to realize healthy and sustainable production of Platycodon grandiflorus - Xiangui Mei; Lin Zhang; Hongbo Xu; Chuanzhi Kang; Wenshuai Sun; Lixiang Zhu; Yingying Cui; Lanping Guo (Journal of Cleaner Production, 2025)

Unearthing Vertical Stratified Archaeal Community and Associated Methane Metabolism in Thermokarst Sediments - Ze Ren; Mei Wang; Jinlei Yu; Lixiang Zhang; Zhenmei Lin; Xia Li; Yunlin Zhang (Environmental Microbiology, 2025)
Thermokarst lakes are hotspots for greenhouse gas emissions across the Arctic and Qinghai‐Tibet Plateau. Investigating the vertical stratification of archaeal communities in thermokarst lake sediments is essential for understanding their ecological roles and contributions to methane production. Here, we analysed archaeal communities along a depth gradient in thermokarst lake sediments. Alpha diversity (richness and Shannon index) generally decreased with depth. Euryarchaeota was the most abundant phylum, though its relative abundance declined with depth, while Thaumarchaeota increased. At the order level, Methanosarcinales and Nitrosopumilales showed increased relative abundance with depth, indicating adaptation to deeper anoxic layers, whereas Methanomicrobiales and Methanotrichales decreased. Beta diversity increased with depth, shifting from stochastic to deterministic processes. Network topology revealed reduced species connectivity but heightened modularity at depth, signalling niche specialisation. Functionally, genes associated with the initial steps of methane metabolism ( Fwd , Mtd , Mer ) increased with depth, while those involved in later steps ( Mtr , Mcr ) decreased, suggesting reduced energy conservation efficiency and lower overall methanogenesis rates in deeper sediments. These findings highlight the significant impact of vertical stratification on archaeal community structure, interaction networks, and functional capabilities.

HDFormer: A transformer-based model for fishing vessel trajectory prediction via multi-source data fusion - Siyuan Lin; Yufei Jiang; Feng Hong; Lixiang Xu; Haiguang Huang; Bin Wang (Ocean Engineering, 2025)

First insight of the intergenerational effects of tri-n-butyl phosphate and polystyrene microplastics to Daphnia magna - Xiaoli Chen; Yijing Gan; Xinlu Yang; Lixiang Zhong; Menghuan Zhang; Mingfu Lin; Xian Qing; Jun Wang; Yumei Huang (Science of The Total Environment, 2024)

Synthesis of stable mesoporous Zr-MOFs using pyrazine-containing ligand for efficient capture of Pb(II) in wastewater - Lixiang Liu; Laidi Wu; Yue Chen; Yongfei Ma; Li Lin; Shuo Li; Xiujuan Yang; Hui Chen; Guojian Duan (Journal of Environmental Chemical Engineering, 2024)

An asymmetric electrode matching reversible kinetics of oxygen reaction for a rechargeable Zn-air battery - Shuxin Li; Han Zhang; Lin Wu; Hongwei Zhao; Lin Tao; Lixiang Li; Chengguo Sun; Dongying Ju; Baigang An (Chemical Engineering Journal, 2024)

The regulation mechanism of hematopoiesis during ischemic and hemolytic anemia in grass carp(Ctenopharyngodon idella) - Lixiang Wei; Yanhan Bai; Rishen Liang; Junyan Lin; Minxuan Yang; Ying Tang; Hong Chen; Minshan Yao; Yao Huang; Li Lin; Zhendong Qin (Aquaculture, 2023)

The study on the main mode of the death of red blood cells in grass carp (Ctenopharyngodon idella) - Hong Chen; Minshan Yao; Ying Tang; Lixiang Wei; Junyan Lin; Fei Shi; Fanbin Zhan; Yanan Li; Jun Li; Li Lin; Zhendong Qin (Aquaculture, 2023)

Study on the regulatory mechanism of erythropoietin in erythropoiesis in grass carp (Ctenopharyngodon idella) - Junyan Lin; Lixiang Wei; Minshan Yao; Hong Chen; Ying Tang; Fei Shi; Fanbin Zhan; Yanan Li; Jun Li; Li Lin; Zhendong Qin (Aquaculture, 2023)

Gedunin Degrades Aggregates of Mutant Huntingtin Protein and Intranuclear Inclusions via the Proteasomal Pathway in Neurons and Fibroblasts from Patients with Huntington’s Disease - Weiqi Yang; Jingmo Xie; Qiang Qiang; Li Li; Xiang Lin; Yiqing Ren; Wenlei Ren; Qiong Liu; Guomin Zhou; Wenshi Wei; Hexige Saiyin; Lixiang Ma (Neuroscience Bulletin, 2019)

Preface: Groundwater in Sub-Saharan Africa - Yongxin Xu; Paul Seward; Cheikh Gaye; Lixiang Lin; Daniel O. Olago (Hydrogeology Journal, 2019)

Determination of groundwater sustainable yield using a numerical modelling approach for the Table Mountain Group sandstone aquifer, Rawsonville, South Africa - Lixiang Lin; Haili Lin (Hydrogeology Journal, 2019)

A typical groundwater storage assessment in the Tugela area, South Africa - Haili Lin; Lixiang Lin (Hydrogeology Journal, 2019)

The diagnostic plot analysis of artesian aquifers with case studies in Table Mountain Group of South Africa - Xiaobin Sun; Yongxin Xu; Lixiang Lin (Hydrogeology Journal, 2015)

Interactions of Denitrifying Bacteria, Actinomycetes, and Fungi on Nitrate Removal in Mix-Culturing Systems - Xiurong Lin; Lixiang Cao; Jian Xiong; Renduo Zhang (Water, Air, & Soil Pollution, 2012)

Changes of Sodium Iodide Symporter Regulated by IGF-I and TGF-β1 in Mammary Gland Cells from Lactating Mice at Different Iodine Levels - Xue Yu; Hongmei Shen; Lixiang Liu; Lin Lin; Meili Gao; Shinan Wang (Biological Trace Element Research, 2012)

Construction of NF-κB-targeting RNAi adenovirus vector and the effect of NF-κB pathway on proliferation and apoptosis of vascular endothelial cells - Gang Chen; Yufang Qiao; Jin Yao; Qiqin Jiang; Xu Lin; Feng Chen; Fenghui Lin; Miao Lin; Lixiang Lin; Pengli Zhu (Molecular Biology Reports, 2011)

The effect of NF-κB pathway on proliferation and apoptosis of human umbilical vein endothelial cells induced by intermittent high glucose - Gang Chen; Yufang Chen; Haifeng Chen; Liantao Li; Jin Yao; Qiqin Jiang; Xu Lin; Junping Wen; Lixiang Lin (Molecular and Cellular Biochemistry, 2011)

Regulation of GSK-3 beta in the proliferation and apoptosis of human thyrocytes investigated using a GSK-3 beta-targeting RNAi adenovirus expression vector: involvement the Wnt/beta-catenin pathway - Gang Chen; Qiqin Jiang; Zhenhui You; Jin Yao; Lunpan Mou; Xu Lin; Xiaoyan Shen; Tingting You; Qiang Lin; Junping Wen; Lixiang Lin (Molecular Biology Reports, 2010)

High FFA-induced proliferation and apoptosis in human umbilical vein endothelial cell partly through Wnt/β-catenin signal pathway - Penli Zhu; Gang Chen; Tingting You; Jin Yao; Qiqin Jiang; Xu Lin; Xiaoyan Shen; Yufang Qiao; Lixiang Lin (Molecular and Cellular Biochemistry, 2010)